Pionnière, à son insu - Paul Bouffartigue (La Nouvelle Revue du Travail)
The film features long excerpts from a spring 2004 interview with a 55 year old postwoman who was first recruited for this job in 1982. Despite pioneering the feminisation of her profession, which only started hiring women in 1975, the protagonist Guylaine does not see herself as a trailblazer, especially since there are as many women as men doing this kind of work nowadays. Guyslaine’s interview demonstrates how a feminisation process could occur without gender discrimination being particularly visible.